Environmental awareness and guests' intention to visit green hotels: The mediation role of consumption values. - Mustafa Demir; Husam Rjoub; Mehmet Yesiltas (PLoS ONE, 2021)
The paper aimed at examining the influence of consumer's environmental awareness on their intention to visit green hotels in north Cyprus, the mediation role of consumption values. Research on eco-friendly hotels stressed that conventional hotels do not make available to consumers the environmental awareness and consumption values, whereas, there is possibility that these benefits might not sit well with the hotel potential consumers. Aside highlighting the features of green hotels, it is imperative to examine how consumers perceive consumption values. A questionnaire-based survey was used to examine the study's objectives. A total of 400 customers at 20 five-stars hotels that were randomly selected across the 3 big cities in north Cyprus (Girne, Lefkosa, and Magusa) were approached and invited to participate. The structural model was tested using structural equation modeling (SEM). The configuration model was analyzed using the partial least square (PLS) method. The finding from the SEM results shows that environmental concern directly and positively influenced the guests' intentions to visit hotels in north Cyprus. Moreover, functional and emotional values were found to mediate the relationship between environmental concern and knowledge on the guests' intention to visit north Cyprus hotels. Finally, the study suggest that the research will be of benefit to the managers of hotels in north Cyprus to know the significance of developing consumer's green awareness and to market it to the customers.